2012
DOI: 10.1007/s00442-012-2252-9
|View full text |Cite
|
Sign up to set email alerts
|

Rodent seed predation: effects on seed survival, recruitment, abundance, and dispersion of bird-dispersed tropical trees

Abstract: Tropical tree species vary widely in their pattern of spatial dispersion. We focus on how seed predation may modify seed deposition patterns and affect the abundance and dispersion of adult trees in a tropical forest in India. Using plots across a range of seed densities, we examined whether seed predation levels by terrestrial rodents varied across six large-seeded, bird-dispersed tree species. Since inter-specific variation in density-dependent seed mortality may have downstream effects on recruitment and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…That is probably because of that the presence of animals such as birds, bats, and rodents feeding the fruits. Other study showed that the presence of rodents in tropical forest will contribute in recruitments of plants and its distribution (Velho, Isvaran, & Datta, 2012). Then, the animals play a crucial role in seed dispersals of those species (Chapman & Chapman, 1995).…”
Section: Conspecific Association Between Small Individuals and Large mentioning
confidence: 97%
“…That is probably because of that the presence of animals such as birds, bats, and rodents feeding the fruits. Other study showed that the presence of rodents in tropical forest will contribute in recruitments of plants and its distribution (Velho, Isvaran, & Datta, 2012). Then, the animals play a crucial role in seed dispersals of those species (Chapman & Chapman, 1995).…”
Section: Conspecific Association Between Small Individuals and Large mentioning
confidence: 97%
“…However, seeds that fall beneath nest trees are also vulnerable to predation by rodents. Recent studies have established the high levels of predation by rodents on Horsfieldia seeds [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies of inter-annual variation in seed production are needed to determine whether the species is a mast fruiting species [21]. Seed predation is an important factor affecting seed survival [50,51], but further studies are required to understand the role of abiotic factors in determining the recruitment and adult tree distribution of this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic factors can also influence dynamics of the stand where flora and fauna have functioned as either facilitation or competition (Velho et al 2012). In the tropical rainforest, many trees grow in the same area resulting in competition to get a place.…”
Section: Introductionmentioning
confidence: 99%